How the Euro was saved - Spiegel, Peter (The Financial Times, 2014)
A vivid and authoritative account of how the eurozone crisis was laid to rest but left a sullen Europe in its wake. This ebook expands and updates an investigation published by the Financial Times in 2014. Peter Spiegel, the newspaper's bureau chief in Brussels, takes the reader deep into the corridors of power to tell a piece of history that will go down as one of Europe's defining moments. How the Euro was Saved is required reading for anyone with an interest in European history and current affairs and follows in the footsteps of the FT's best selling ebook, If Greece goes ...